The Ritual Origins of Native Law in Sabah and Future Implications: The Case of The Kimaragang - Jikat Binol Darimbang; Jacqueline Pugh-Kitingan; Gaim James Lunkapis (Faculty of Arts and Social Sciences, University of Malaya, 2023)
Malaysia has three official recognised judicial systems of equal standing—the Civil Courts, the Syariah Courts, and the Native Courts of Sabah and Sarawak. While the Civil Courts have a punitive system of justice, especially for handling criminal cases, the Native Courts have a restorative system of justice that in Sabah is largely based on atonement through blood sacrifices or sogit. The sogit systems of the Native Courts in each administrative District vary according to ethnic group and culture but developed from the belief systems and traditional indigenous religions that acknowledged the existence of a benevolent Creator. Based on ethnographic research, including participant observation and interviews with key informants, as well as focus group interviews, this article focuses on the ritual origins of the Native Court system of the Kimaragang, the main Dusunic ethnic group of Kota Marudu District in northern Sabah. It explores the Monogit Pomogunan, a traditional ritual series performed by boboliyan or priestesses to cleanse the world from pandemics such as COVID-19 that are believed to occur due to human wrongdoing. This is linked to the sogit system of the Native Court of Kota Marudu for the Kimaragang. The implications of the ritual origins of the sogit system and the cultural identity of the Kimaragang are discussed in light of the importance of cultural heritage continuity and against calls to standardise the sogit systems for all the Native Courts in Sabah.